2015
DOI: 10.1007/s12031-015-0635-1
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Protects Against Asymmetric Dimethylarginine-Induced Apoptosis in the Cultured Human Brain Microvascular Endothelial Cells

Abstract: Asymmetric dimethylarginine (ADMA) is emerging as a key contributor to endothelial dysfunction. The drug probucol was reported to have an anti-lipid peroxidation effect and improve endothelial dilation function. But little is known about the protective effect of probucol on ADMA-induced human brain microvascular endothelial cell (HBMEC) injury and its underlying mechanisms. Therefore, in this study, we investigated the effect of probucol on ADMA-induced HBMEC injury and its potential mechanisms. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Our present results revealing the opposite effect of exercise and hypertension on both cerebrovascular BDNF and P-eNOS ser1177 and a stimulating effect of an NO donor on cerebrovascular BDNF production argue for an in vivo control of cerebrovascular BDNF production by NO derived from cerebral endothelium. These data resonate with studies that reported lower BDNF levels in cultured microvascular endothelial cells exposed to the endogenous eNOS inhibitor asymmetric dimethyl arginine (ADMA) (Ma et al 2015) or to advanced glycosylation products (Navaratna et al 2011), which act as NO scavengers (Bucala et al 1991). They also could explain the reduction of brain BDNF levels reported after genetic and pharmacological eNOS inhibition (Chen et al 2005, Banoujaafar et al 2014.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our present results revealing the opposite effect of exercise and hypertension on both cerebrovascular BDNF and P-eNOS ser1177 and a stimulating effect of an NO donor on cerebrovascular BDNF production argue for an in vivo control of cerebrovascular BDNF production by NO derived from cerebral endothelium. These data resonate with studies that reported lower BDNF levels in cultured microvascular endothelial cells exposed to the endogenous eNOS inhibitor asymmetric dimethyl arginine (ADMA) (Ma et al 2015) or to advanced glycosylation products (Navaratna et al 2011), which act as NO scavengers (Bucala et al 1991). They also could explain the reduction of brain BDNF levels reported after genetic and pharmacological eNOS inhibition (Chen et al 2005, Banoujaafar et al 2014.…”
Section: Discussionsupporting
confidence: 86%
“…These data resonate with studies that reported lower BDNF levels in cultured microvascular endothelial cells exposed to the endogenous eNOS inhibitor asymmetric dimethyl arginine (ADMA) (Ma et al . ) or to advanced glycosylation products (Navaratna et al . ), which act as NO scavengers (Bucala et al .…”
Section: Discussionmentioning
confidence: 99%
“…e antioxidant and anti-inflammatory properties of probucol have been investigated using in vitro cell cultures and in vivo animal models [13,14]. It inhibits extracellular ROS and effectively reduces vascular endothelial cell apoptosis caused by oxidative stress damage [25]. Probucol reduces hypoxia-induced angiogenesis by improving the function of endothelial progenitor cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a positive control by endothelium-derived NO of BDNF synthesis by cerebral endothelial cells is not surprising. Indeed, the exposure of cultured brain-derived endothelial cells to inhibitors of NO production including the peptide A beta (a compound largely involved in the physiopathology of Alzheimer disease) and ADMA (an endogenous eNOS inhibitor) was reported to decrease BDNF production (Guo et al, 2008 ; Ma et al, 2015 ). In the same vein, incubation of isolated cerebral microvessels with advanced glycation-end products (Navaratna et al, 2011 ) that act as NO scavengers (Bucala et al, 1991 ) resulted in BDNF downregulation whilst their incubation with a slow releasing NO donor was recently reported by our laboratory to increase BDNF production (Monnier et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%